2002
DOI: 10.4049/jimmunol.168.8.3910
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of IL-1 Receptor-Associated Kinases by Lipopolysaccharide

Abstract: IL-1R-associated kinase (IRAK) plays a pivotal role in IL-1R/Toll-like receptor (TLR)-mediated signaling and NF-κB activation. IRAK from leukocytes undergoes rapid activation and inactivation/degradation following IL-1 or LPS stimulation. The rapid degradation of IRAK may serve as a negative feedback mechanism of down-regulating IL-1R/TLR-mediated signaling and cytokine gene transcription. Although IL-1/IL-1R-triggered IRAK degradation has been studied in detail, the mechanism of LPS-induced IRAK activation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
65
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 36 publications
3
65
1
Order By: Relevance
“…The direct interaction between p62 and the adapter protein TRAF6, which play a crucial role in signaling through IL-1␤ and TLR2, may account for the involvement of aPKCs in different NF-B activation pathways. Hu et al (30) showed direct interaction of IRAK1, a serine/threonine kinase upstream of TRAF6, with PKC when monocytic cells were stimulated with LPS. Using a TLR2-dependent stimulus, we did not detect an association of PKC with IRAK1, IRAK4, or TRAF6.…”
Section: Discussionmentioning
confidence: 99%
“…The direct interaction between p62 and the adapter protein TRAF6, which play a crucial role in signaling through IL-1␤ and TLR2, may account for the involvement of aPKCs in different NF-B activation pathways. Hu et al (30) showed direct interaction of IRAK1, a serine/threonine kinase upstream of TRAF6, with PKC when monocytic cells were stimulated with LPS. Using a TLR2-dependent stimulus, we did not detect an association of PKC with IRAK1, IRAK4, or TRAF6.…”
Section: Discussionmentioning
confidence: 99%
“…In examining this question, an important lead was provided by the findings that PKC-associated with IRAK in LPS-treated THP-1 cells and the demonstration that PKC activity was required for LPS-induced IRAK degradation (40). These results, indicating a possible role for PKC-in a pathway regulating IRAK degradation, led us to examine whether this may be regulated by PI 3-kinase because LPS has been shown to activate this lipid kinase leading to activation of PKC- (39).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work from this laboratory (36) and elsewhere (37,38) has demonstrated that the interaction of the complex of both LPS and LPS-binding protein with CD14 brings about activation of PI 3-kinase, which appears to be involved in mediating cellular responses to endotoxin including activation of an atypical isoform of PKC, PKC- (39). These findings, coupled with the observations that PKC-associates with IRAK in LPS-treated cells and that the PKC inhibitor calphostin prevents IRAK degradation (40), provide a basis for a model in which cellular responsiveness to LPS involves a PI 3-kinase signaling pathway that functionally bifurcates. In this model, one arm of a PI 3-kinase pathway leads to cell activation in response to LPS.…”
mentioning
confidence: 83%
“…4C). In addition, the lack of detecting IRAK-M at 30 min following LPS stimulation is expected because of the natural clearance or degradation of IRAK-1 following LPS stimulation (Hu et al, 2002;Jensen and Whitehead, 2001;Yamin and Miller, 1997). Therefore, α-MSH suppresses LPS-stimulated TLR4 activity through a mechanism that promotes IRAK-M binding of IRAK-1.…”
Section: The Effects Of α-Msh On Tlr4 Signaling In Macrophagesmentioning
confidence: 99%